Dimensions of Consumers’ Advertising Beliefs in India - Vij, Sandeep; Singh, Raghbir (Indian Journal of Marketing, 2011)
This paper identifies the belief dimensions for Indian consumers’ attitude toward advertising. A sample of 873 consumers including 458 males and 415 females has been drawn from North Indian States and Union Territories. The 28 belief statements in Pollay and Mittal Model of attitude toward advertising have been factor analysed (Principal Component Analysis with Orthogonal Rotation) to explore the dimensionality of advertising beliefs of Indian consumers. Six dimensions of Indian consumers’ beliefs about advertising have been identified and explained. These are ’Harmful for Society’, ’Good for Economy, ’Better Quality of Life’, ’Manipulative’, ’Lower Prices’, and ’Hedonic Pleasure’. Implications of advertising beliefs for advertisers and marketers have also been discussed.